Wow feeling effect on repeat visit intention with special reference to five star hotels in down south - Sammani, U.G.O. (Faculty of Management Studies and Commerce, University of Jaffna, Sri Lanka, 2019)
Tourism is the largest service oriented industry in the world. Repeat visitation is derived from customer satisfaction which is an essential element for survival of the tourism industry. Identification of most valued attributes is fundamental to attract and retain satisfied customers. Wow feeling has identified as the most important factor that can be increased the tourists’ satisfaction. Accordingly, this study focuses to identify the areas where can be generated wow feeling at the hotels and further it develops to identify the relationship between wow feeling and the repeat visit intention of tourists. To conduct this study, it was selected the five star hotels in Down South. The repeat guests visited the hotels during the period of November 2017toFebruary 2018 were considered as the population of the study. Out of the total repeat tourists visited the hotels during the prescribed period; it was selected 300 foreign and local tourists to the sample following the purposive sampling technique. Self-structured questionnaire was used to collect primary data. Pearson correlation analysis and the multiple linear regression analysis were used to analyze the data. According to the study findings, it was able to find out that there is a strong positive relationship between wow feeling and repeat visit intention among tourists. Further, the study focuses that welcome, restaurant and bar and cleanliness are highly impact on tourists when generating more wow feeling at the hotels. Finally, the study recommended that the hotels needed to be taken actions to enhance the customer loyalty and their satisfaction to ensure the repeat visitations. Hotels’ management needed to implement future actions in their corporate plans to uplift the conditions of the hotels and needed to develop sustainable strategic plans for the hotels while satisfying their customers in their maximum.
Keywords: Wow Feeling Effect; Repeat Visit Intention; Valued Attributes